Вариант 2
у=-2х+3
Чтобы получить у=9, подставляем в функцию х=-3:
-2(-3)+3=6+3=9
Чтобы получить х=2, подставляем в функцию у=-1:
-2х+3=-1
-2х=-1-3
-2х=-4
х=2
Чтобы получить у=2, подставляем в функцию х=0,5:
-2*0,5+3=-1+3=2
Чтобы получить х=-0,5, подставляем в функцию у=4:
-2х+3=4
-2х=1
х=-1/2
Чтобы получить у=3, подставляем в функцию х=0:
-2*0+3=3
Чтобы получить х=1,5, подставляем в функцию у=0:
-2х+3=0
-2х=-3
х=3/2=1,5
Вариант 2
у=-2х+3
Чтобы получить у=9, подставляем в функцию х=-3:
-2(-3)+3=6+3=9
Чтобы получить х=2, подставляем в функцию у=-1:
-2х+3=-1
-2х=-1-3
-2х=-4
х=2
Чтобы получить у=2, подставляем в функцию х=0,5:
-2*0,5+3=-1+3=2
Чтобы получить х=-0,5, подставляем в функцию у=4:
-2х+3=4
-2х=1
х=-1/2
Чтобы получить у=3, подставляем в функцию х=0:
-2*0+3=3
Чтобы получить х=1,5, подставляем в функцию у=0:
-2х+3=0
-2х=-3
х=3/2=1,5